Criterion validation and interpretability of the Single Assessment Numerical Evaluation (SANE) of self-reported recovery in patients with neck pain. (December 2021) - O'Halloran, Bryan; Cook, Chad E.; Oakley, Elizabeth
Abstract: Background: The SANE is a PROM of recovery, which may assist clinicians in clinical decision-making and discharge planning. The psychometric measurement properties of the SANE have yet to be determined for neck pain. Objectives: Threefold objectives included: 1)determine the numerical threshold for the SANE at which patients with neck pain determine their symptoms are acceptable; 2)determine the association between scores for the NDI and VAS, with the SANE; 3)determine the average number of visits, costs and value associated with the management of neck pain. Design: Longitudinal repeated measures cohort design. Methods: Threshold measures for self-reported recovery with the SANE anchored to the PASS were examined using ROC. PCC determined the relationship between the VAS/pain and NDI raw/percentage change scores and the SANE at discharge. Descriptive statistics were used for number of visits and cost. Value was calculated as the proportion of change on the NDI and VAS/$100 US dollars spent. Results: 57 subjects completed full observation. ROC analysis indicates a threshold value of 82.5%(Sn = 56.0, Sp = 85.7, +LR = 1.68, -LR = 0.29) on the SANE with an AUC of 0.820(95%CI = 0.638, 1.00). A weak correlation was found between raw NDI(r = 0.39 p < 0.05)/Pain(r = 0.45 p < 0.05) scores and the SANE with a moderate correlation between percent change scores of NDI(r = 0.52 p < 0.05)/PAIN(r = 0.54 p < 0.05) and the SANE. The value proposition indicated cost of care amounted to a 10.5% and 12.9%; improvement in the NDI and pain scores/$100 spent. Conclusions: Patients reporting greater than 82.5% on the SANE are likely to find their present status acceptable and potentially stop seeking care. Highlights: The SANE value of 82.5% reflects a patients unlikelihood of seeking further care. The SANE reflects recovery rather than improvement. Change of 10–12% is expected in pain and function for neck pain per $100 spent on care. Cost of care data indicates an expectation of change of 12.9% improvement in the VAS Pain score per $100 spent. This study provides a unique measure of value for care for neck pain.